Pengaruh Optimal Konsentrasi Ekstrak Tomat dan BAP terhadap Pertumbuhan Planlet Dendrobium sutiknoi Secara In Vitro - Laras Ayuningtias; Aminatun Munawarti; Nurul Qur’ani (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Dendrobium sutiknoi orchids are in high demand in Indonesia, but cultivation is still relatively slow. Conventional propagation of orchid plants to obtain seedlings requires a reasonably long time, so tissue culture techniques are used to obtain quality orchid seedlings relatively quickly. This study aims to analyze the optimal concentration of adding tomato extract and the plant growth regulator BAP (6-Benzylaminopurine) on the growth of D. sutiknoi orchids. This research is an experimental study using a Completely Randomized Design (CRD) with two factors: tomato extract (10%, 15%, and 20%) and BAP hormone (1, 2, and 3 ppm). All treatments were repeated 3 times. This research was conducted in 2024 and involved several observation parameters such as the number of roots, leaves, shoots, plant height, root length, and fresh weight of plantlets. The results showed that adding tomato extract and BAP hormone significantly affected the growth and development of the D. sutiknoi orchid plantlets. The treatment combination with 15% tomato extract and two ppm BAP resulted in the highest values for the number of roots, leaves, shoots, plant height, root length, and fresh weight of the plantlets.